An engineered yeast efficiently secreting penicillin. - Loknath Gidijala; Jan A K W Kiel; Rutger D Douma; Reza M Seifar; Walter M van Gulik; Roel A L Bovenberg; Marten Veenhuis; Ida J van der Klei (PLoS ONE, 2009)
This study aimed at developing an alternative host for the production of penicillin (PEN). As yet, the industrial production of this beta-lactam antibiotic is confined to the filamentous fungus Penicillium chrysogenum. As such, the yeast Hansenula polymorpha, a recognized producer of pharmaceuticals, represents an attractive alternative. Introduction of the P. chrysogenum gene encoding the non-ribosomal peptide synthetase (NRPS) delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine synthetase (ACVS) in H. polymorpha, resulted in the production of active ACVS enzyme, when co-expressed with the Bacillus subtilis sfp gene encoding a phosphopantetheinyl transferase that activated ACVS. This represents the first example of the functional expression of a non-ribosomal peptide synthetase in yeast. Co-expression with the P. chrysogenum genes encoding the cytosolic enzyme isopenicillin N synthase as well as the two peroxisomal enzymes isopenicillin N acyl transferase (IAT) and phenylacetyl CoA ligase (PCL) resulted in production of biologically active PEN, which was efficiently secreted. The amount of secreted PEN was similar to that produced by the original P. chrysogenum NRRL1951 strain (approx. 1 mg/L). PEN production was decreased over two-fold in a yeast strain lacking peroxisomes, indicating that the peroxisomal localization of IAT and PCL is important for efficient PEN production. The breakthroughs of this work enable exploration of new yeast-based cell factories for the production of (novel) beta-lactam antibiotics as well as other natural and semi-synthetic peptides (e.g. immunosuppressive and cytostatic agents), whose production involves NRPS's.